NICE guideline review: type 2 diabetes in children and young people – diagnosis and management (NG18) - Weber, Isabella; Fisher, Benjamin G; Myles, Cliodhna; Hendriks, A Emile J; Marcovecchio, M Loredana (Archives of disease in childhood. Education and practice edition, 2025)
Correspondence to Dr Isabella Weber; isabella.weber1@nhs.net Background Type 2 diabetes (T2D) is becoming progressively more common among young people concomitantly with the epidemic of childhood obesity.1 The incidence of youth-onset T2D is projected to rise by >600% by 2060,2 and the UK has the fastest increase in incidence rate globally.3 Compared with type 1 diabetes (T1D), youth-onset T2D is associated with higher rates and earlier onset of complications and a 50% higher mortality rate.1 Appropriate intervention is therefore key to improve outcomes.4 Information about the current guideline In May 2023, the National Institute for Health and Care Excellence (NICE) updated the section on T2D of the guideline on ‘Diabetes (type 1 and type 2) in children and young people: diagnosis and management’.5 Additionally, relevant guidelines have been recently published by the (UK) Association of Children’s Diabetes Clinicians (ACDC) and the International Society for Pediatric and Adolescent Diabetes (ISPAD) (box 1). Box 1 Resources National Institute for Health and Care Excellence (NICE) guideline (2023)5: https://www.nice.org.uk/guidance/ng18 Association of Children’s Diabetes Clinicians (ACDC) guideline (2023): https://www.a-c-d-c.org/wp-content/uploads/2012/08/TYpe-2-guideline-ACDC-format-publish-2.pdf International Society for Pediatric and Adolescent Diabetes (ISPAD) guideline (2022): https://www.ispad.org/page/ISPADGuidelines2022 Key issues the guideline addresses Immediate actions at T2D diagnosis A child or young person (CYP) with suspected T2D should be referred to a multidisciplinary paediatric diabetes team to ‘confirm diagnosis and provide immediate and continuing care’ (box 2).5 CYP with T2D should be given tailored information about T2D and offered dietary advice and support including weight management, metformin therapy and equipment for capillary blood glucose (BG) monitoring. Weight management remains the cornerstone of T2D management. [...]it is essential to provide advice for a healthy lifestyle, including diet and exercise. Provide psychological support and ensure access to mental health services, if required.